1998
DOI: 10.1007/s003300050602
|View full text |Cite
|
Sign up to set email alerts
|

The anterior tilt of the acromion: radiographic evaluation and correlation with shoulder diseases

Abstract: The aim of this study was to test whether the anterior tilt of the acromion can be objectively evaluated on lateral radiographs, and whether there is a relation between this anatomical feature and the most common shoulder diseases. Lateral radiographs of 15 dried scapulas were performed in neutral position and with 5 degrees of caudal, cranial, anterior and posterior angulations. Two hundred and forty-three shoulders, both asymptomatic and affected by chronic and post-traumatic impingement, calcific tendinitis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
48
1
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(53 citation statements)
references
References 18 publications
3
48
1
1
Order By: Relevance
“…Aoki et al [3] found that patients with impingement had a significantly flatter slope of the acromion as viewed on lateral radiograph compared to those of asymptomatic patients. Other studies have also described morphologic features of the acromion, the coracoid and coracoacromial arch as risk factors for impingement syndrome leading to cuff disease [ 1,4,9, 1 1,13,17, 22,23,25,30,32]. However, further criteria are still needed to better identify individuals at risk for RC tears or to predict which part of the cuff is likely to fail.…”
Section: Introductionmentioning
confidence: 99%
“…Aoki et al [3] found that patients with impingement had a significantly flatter slope of the acromion as viewed on lateral radiograph compared to those of asymptomatic patients. Other studies have also described morphologic features of the acromion, the coracoid and coracoacromial arch as risk factors for impingement syndrome leading to cuff disease [ 1,4,9, 1 1,13,17, 22,23,25,30,32]. However, further criteria are still needed to better identify individuals at risk for RC tears or to predict which part of the cuff is likely to fail.…”
Section: Introductionmentioning
confidence: 99%
“…Regardless of the direction of the upper extremity, the humeral head needs minimal subacromial space lest it should impinge against the glenoid fossa. The humeral head has stability and mobility due to shoulder external rotation (infraspinatus and teres minor) 32) . Shoulder external rotation is certainly needed for the supraspinatus and tendon to freely be moved as patients raise or stretch out their arms.…”
Section: Discussionmentioning
confidence: 99%
“…As patients with an unstable shoulder elevate their upper limbs, shoulder impingement occurs 32) . Regarding this issue, Rajaratnam et al 12) argued the necessity of a dynamic test for the shoulder joint to test stroke patients as they elevate their upper limbs.…”
Section: Discussionmentioning
confidence: 99%
“…갈고리형태의 견봉이 충돌증후군 및 회전근개 파열과 상관성이 있다는 예 1,2,6,8, 16,17,[25][26][27]29) 와 연관성을 부정하는 연구결과 4,10,14,20,22,28) 가 있다. 더욱이 견봉의 단순 방사선 영상은 관찰자간 오차가 보고되었다 11,12,24) . 하지만 아직 견봉의 회전근개 자극은 충돌증후군의 중요한 발생원인 으로 고려된다 17,21,26) .…”
Section: 서 론unclassified